Macroinvertebrates living on Eichhornia azurea Kunth in the Paraguay River - Poi, Alicia Susana G. (2003)
Macroinvertebrates living on Eichhornia azurea Kunth in the Paraguay River. Ten sites along the Paraguay River fringing floodplain, from Porto Cáceres to the confluence with the Paraná River, were sampled during high (June-July 1995) and low (December 1995) water periods in order to explain the abundance and proportion of functional feeding groups of macroinvertebrates living on Eichhornia azurea. The mean abundance of macroinvertebrates varied between 3,565 ind.m-2 and 25,145 ind.m-2 . Depending on the sampling sites insects larvae (Chironomidae and Hydroptilidae) or crustaceans (Lepthesteridae) were the main representative taxa. Similarity between the morpho species of invertebrates was quite high for sites located in the Upper (from the headwater to the Appa River) and the Lower Paraguay. During high water, filtering collectors (FC) dominated and constituted over 40% of total abundance. The ratio FC/GC varied between 2.1 and 6.2 and the ratio SC/SH+Total Collectors between 0.06 and 0.2. At low water there were proportionally more collector-gatherers (GC) predators or scrapers (SC). In comparison with the high water period, the ratio FC/ GC decreased and the ratio SC/SH+Col increased. Shredders (SH) were fewer in number during both hydrological periods. Although no significant relationship was found between total abundance of macroinvertebrates and hydrological periods, functional group analysis is sensitive to changes in the importance of the food resource (detritus, periphyton,macrophytes or prey ) during low and high water periods.